2022
DOI: 10.3390/rs14143486
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale LBP Texture Feature Learning Network for Remote Sensing Interpretation of Land Desertification

Abstract: Land desertification is a major challenge to global sustainable development. Therefore, the timely and accurate monitoring of the land desertification status can provide scientific decision support for desertification control. The existing automatic interpretation methods are affected by factors such as “same spectrum different matter”, “different spectrum same object”, staggered distribution of desertification areas, and wide ranges of ground objects. We propose an automatic interpretation method for the remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…To deal with this problem, we have two options, one is to add additional data sources [57], and the other is to extract more complex features. Without additional data sources, spectral confusion can be reduced by more comprehensive features (combined with spectral, spatial, and texture features) [11,58]. Table 1 provides a summary of the strengths and limitations of these extraction units, with the relevant literature.…”
Section: Object-based Methodsmentioning
confidence: 99%
“…To deal with this problem, we have two options, one is to add additional data sources [57], and the other is to extract more complex features. Without additional data sources, spectral confusion can be reduced by more comprehensive features (combined with spectral, spatial, and texture features) [11,58]. Table 1 provides a summary of the strengths and limitations of these extraction units, with the relevant literature.…”
Section: Object-based Methodsmentioning
confidence: 99%
“…However, with the deepening of research in recent years, compared with desertification in other parts of northern China, some scholars believe that the change in the amount of water resources transported downstream and controlled by the glaciers and snow in the Qilian Mountains, namely, water supply in the source area, is the key factor for the formation and evolution of sand dunes and the desertification in the Hexi Corridor (Xie et al, 2004). In addition, some studies have suggested that the weakening of large-scale wind activity in northern China and even the NH and the acceleration of regional water cycle (increasing water supply) jointly restrict the dune dynamics and desertification process in the Hexi area (Wang et al, 2002;Wang et al, 2008a;2008b). Taking a further comprehensive view, the above-mentioned formation mechanisms of dune landforms, whether on local scale, regional scale, or even hemispheric scale, can be attributed essentially to a natural mechanism, that is, the sand dunes in the Hexi Corridor are of natural origin.…”
Section: The Formation Mechanism Of Sand Dunes In the Hexi Corridormentioning
confidence: 99%
“…Land desertification is a major ecological problem facing arid and semi-arid regions worldwide [1]. It often occurs in mid-latitude regions, directly or indirectly affects more than 100 countries worldwide, involves more than one billion people, causes losses of up to USD 10 billion per year, and is ranked as one of the most serious environmental and social problems in the world [2,3]. According to the statistics released by the United Nations regarding land desertification, the problem of land desertification faced by China Remote Sens.…”
Section: Introductionmentioning
confidence: 99%